ANALISIS SIKAP PERCAYA DIRI SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MATA PELAJARAN MATEMATIKA - Yunia Hardianti I.W; Muhammad Prayito; Kartinah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the lack self-confidence of students in mathematics. This study aims to analyze self-confidence using the Problem Based Learning model in Mathematics. The sample of this research was 28 students in class 1 of SD Negeri Sawah Besar 01 for the academic year 2022/2023The instrumen used in this study was a non-test. The non-test instrumen used in this study was a questionnaire which was composed of 10 items based on self-confidence indicators consists of four components: self-confidence, assertiveness, responibility, and positive thingking. From the results of the analysis of the indicators of self-confidence, self-confidence obtained results with high criteria, analysis of the assertiveness indicator obtained results with hifh criteria, analysis of the responsibility indicator obtained results with high criteria, and analysis of positive thinking indicators obtained result with high ceriteria. It was concluded that the LKPD in the Problem Based Learning model in Mathematics subject received a positive response from students. This is evidenced by the result of all indicators or self-confidence with high criteria.